Dry Eye Disease in Younger Age - Munir Amjad Baig, Nadir Mehmood, Muhammad Hamaza, Rabeeya Munir (Journal of Rawalpindi Medical College, 2017)
To evaluate the personal and environmental risk factors attributable to dry eye disease (DED) among younger age group of Islamabad. Methods: In this cross-sectional study, 360 individuals aged 18-40 years of either sex were screened randomly. All patients visiting outpatient department with various symptoms and later diagnosed to have abnormal tests and symptoms of dry eye were included in this study. Patients having any eye disease, systemic disease and those using antiallergic or steroid drugs were excluded. Patient demographics and dry eye questionnaire (DEQ) was administered by a trained interviewer. Dry eye tests like tear film breakup time (TBUT), corneal fluorescein staining (CFS), Schirmers test (ST) and slit-lamp examination for presence of conjunctival injection, punctate epithelial erosions (PEE), lid margins plugging and telengiectasias were used to diagnose dry eye. Results:There were 55.6% males and (44.4% females. Majority were urban (72.8%). Major constituents were students (23.3%), teachers (17.2%), office workers (27.8%), housewives (13.9%) and labourers (17.8%). In this study, 81(22.5%) subjects, 42(11.7%)male, 39(10.8%) female were symptomatic defined as presence of one or more dry-eye symptoms often or all the time. Two hundred and two (56.1%) subjects had low TBUT, 140(38.9%) had low ST and 180(50%) patients had abnormal plugging or telengiectasias of lid margins. Common symptoms were burning 59.2%, eye strain 55.5%, watering 51.8% and fatigue 49.3%.Dry eye symptoms were related to computer use 20(24.7%), blepharitis 19(23.4%), refractive errors 7(8.6%), contact lens use 3(3.7%), refractive surgery 1(1.2%), eye make-up use 10(12.3%), use of antiallergic medications 10(12.3%) and smoking 11(13.5%). Conclusion : Various environmental effects at work are related to eye and physical symptoms which affect quality of life. Those students who are using computers and other screens develop dry eye symptoms. Dry eye is a common condition presenting to Ophthalmologists. It is underdiagnosed and variably treated with antiallergic /decongestants drops on empirical basis.